A study on the effect of size and ratio of book value to market value on excessive return - Seyed Mohsen Tabatabaei Mozdabadi; Hossein Mohammadpour Zarandi (Management Science Letters, 2012)
Stock market plays an important role on demonstrating economy direction and it provides good opportunities for people who wish to purchase a small portion of different firms' shares. In this paper, we propose an empirical study to measure the impact of the market size and the ratio of book value on market value on excessive return. The study gathers the necessary information from some of active stock shares traded on Tehran Stock Exchange over the period of 2010-2011. The proposed model of this paper uses linear regression analysis to investigate the relationship between the excessive return and other factors. The study divides the information into seven equal groups and fits the regression model using ordinary least square technique. The results indicate that there is a negative relationship between size and excessive return and a positive relationship between the ratio of BV/MV and excessive return. Although the results of both tests are positive, we have to be more cautious about what have reported on the second hypothesis.